Micro Mirror Polymer Composite Offers Mechanically Switchable Light Transmittance - Rotzetter, Aline C. C.; Fuhrer, Roland; Grass, Robert N.; Schumacher, Christoph M.; Stoessel, Philipp R.; Stark, Wendelin J. (Advanced engineering materials, 2014)
Elastic silicone composites with mechanically switchable transparency are generated by incorporating micron‐sized aluminum platelets into a highly flexible silicone. Physisorbing Fe3O4 nanoparticles onto the platelets surface allow magnetic pre‐alignment during the polymer curing. One‐dimensional or two‐dimensional stretching of the resulting silicone composites permits orientation of the incorporated flakes and alters light transmittance of the polymer coating.